Ehretiquinone from Onosma bracteatum Wall Exhibits Antiaging Effect on Yeasts and Mammals through Antioxidative Stress and Autophagy Induction. (15th January 2021) - Pan, Yanjun; Liu, Yanan; Fujii, Rui; Farooq, Umer; Cheng, Lihong; Matsuura, Akira; Qi, Jianhua; Xiang, Lan
Abstract : The antiaging benzoquinone-type molecule ehretiquinone was isolated in a previous study as a leading compound from the herbal medicine Onosma bracteatum wall. This paper reports the antiaging effect and mechanism of ehretiquinone by using yeasts, mammal cells, and mice. Ehretiquinone extends not only the replicative lifespan but also the chronological lifespan of yeast and the yeast-like chronological lifespan of mammal cells. Moreover, ehretiquinone increases glutathione peroxidase, catalase, and superoxide dismutase activity and reduces reactive oxygen species and malondialdehyde (MDA) levels, contributing to the lifespan extension of the yeasts. Furthermore, ehretiquinone does not extend the replicative lifespan of Δsod1, Δsod2, Δuth1, Δskn7, Δgpx, Δcat, Δatg2, and Δatg32 mutants of yeast. Crucially, ehretiquinone induces autophagy in yeasts and mice, thereby providing significant evidence on the antiaging effects of the molecule in the mammalian level. Concomitantly, the silent information regulator 2 gene, which is known for its contributions in prolonging replicative lifespan, was confirmed to be involved in the chronological lifespan of yeasts and participates in the antiaging activity of ehretiquinone. These findings suggest that ehretiquinone shows an antiaging effect through antioxidative stress, autophagy, and histone deacetylase Sir2 regulation. Therefore, ehretiquinone is a promising molecule that could be developed as an antiaging drug or healthcare product.